Immobilized β-galactosidase onto magnetic particles coated with polyaniline: Support characterization and galactooligosaccharides production - Neri, D. F. M. (2011)
Magnetite particles (<100 μm) obtained by coprecipitation of Fe2+ and Fe3+ and coated with polyaniline (MAG-PANI) were used to immobilize Aspergillus oryzae β-galactosidase via glutaraldehyde. The amount of β-galactosidase immobilized onto MAG-PANI was ca. 2.04 mg/g support. This magnetic enzymatic derivative was capable to act on lactose and to produce tri and tetragalactosides (transgalactosylation) and the catalytic properties were similar to the soluble enzyme. For lactose concentrations up to 100 g/L, no differences were observed in the enzyme specific activity between free and immobilized forms (100% of specific activity retention), but for higher lactose concentrations the initial specific reaction rate of the immobilized form was affected by increasing lactose concentrations. The Activation Energy values for both free and immobilized forms were similar, around 16 ± 1.4 KJ/mol. The tri and tetra-galactosides production by both soluble and immobilized enzyme was not affected by temperature in the range of 30–60 °C. As the initial lactose concentration increased from 5% to 50%, the maximum GOS content in the product increased from 11.2% (at 35% conversion) to 26.1% (at 56% conversion) for the free enzyme and from 10.8% (at 33% conversion) to 26.0% (at 52% conversion) for the immobilized enzyme. The MAG-PANI was characterized by X-ray diffraction, Fourier transform infrared spectroscopy, elemental analyzer, scanning electronic microscope, differential scanning calorimeter, thermogravimetric analyzer, vibrating sample magnetometer and thermomagnetization. These analysis showed rhombohedra particles presenting good magnetic response, evidences for the PANI coating and protein immobilization and magnetite as the predominant component. This magnetic β-galactosidase derivative presents the following advantages: simple synthesis using low cost reagents, catalytic properties similar to the soluble enzyme and easy removal from the reaction mixture by a magnetic field and reuse.